Detection and identification of Chlamydophila psittaci from wild spotted doves in the Klang Valley in Malaysia - Phong , Su Fun; Ideris, Aini; Salim, Nadzri; Al-Ajeeli, Karim Sadun Ali (Veterinary Association Malaysia, 2006)
A total of fifty-six wild spotted doves was captured for the isolation and identification of Chlamydophila psittaci from the Klang Valley in Malaysia. Cloaca swab samples were taken from these doves for Clearview" chlamydia test and found that fourteen (25%) birds tested positive for chlamydiosis. From these fourteen positively infected birds, five showed clinical signs of poor feathering, chilling and diarrhoea. The less positively infected birds showed no clinical signs. Several methods were used for the identification of Chlamydia from the positively infected spotted doves, including indirect immunofluorescent and peroxidase techniques, Giemsa and Gimenez staining, and transmission electron microscopy (TEM). From all these methods, the chlamydia appeared as intracytoplasmic inclusion in the McCoy cell. In the TEM, two morphologically distinct forms of chlamydia, termed elementary body (EB) and reticulate body (RB) were seen in the infected cell.